Working process model development of the gas turbine engine combustor fueling on methanol - Shevchenko, Mykhailo; Ambrozhevich, Maya; Fesenko, Kseniia (Eastern-European Journal of Enterprise Technologies, 2024)
The use of methanol as a fuel for aircraft and stationary gas turbine engines (GTE) is a priority direction in engine building. It is well known that when modeling the GTE performances using first-level mathematical models, there is an error in calculating specific fuel consumption, which is caused by the simplified description of the GTE combustor working process. The object of the study is the working process in the GTE combustor fueling on methanol. The peculiarity of the developed mathematical model of the working process of the GTE combustor is the use of enthalpy dependencies on temperature, pressure, and mixture composition. Enthalpy dependencies in this form implicitly account for the effect of thermal dissociation and allow for the correct formulation of the equivalent combustion reaction path. For two components (H2O and CO2), accounting for pressure leads to the fact that at standard temperature and partial pressures exceeding the saturation pressure, these components exist in a liquid state. This situation, with a constant enthalpy increment in the equivalent process of heating the combustion products from the standard temperature to the temperature at the end of adiabatic heat supply, decreases this temperature. Clarification of the temperature at the combustor outlet leads to changes in all calculated combustor performances, including the combustor fuel air ratio. The calculation results of the fuel air ratio are compared with known experimental data of the General Electric CF6-80A engine combustor (USA). The average calculation error of the fuel air ratio does not exceed 4 %. The developed model can be implemented in existing and developing mathematical models of gas turbine engines for temperatures at the end of the combustion process below 2,600 K